Pembatalan Perkawinan Akibat Paksaan (Studi Putusan No.1671/Pdt.G/2024/PA.Sr): Annulment of Marriage due to Coercion (a Study of Decision No. 1671/pdt.G/2024/PA. Sr) - Erli Elvina Dzakiyyah Iman; Dian Septiandani; Amri Panahatan Sihotang (Hukum dan Masyarakat Madani, 2026)
This study aims to analyze the legal reasoning of the judges and the legal consequences of the annulment of marriage on the grounds of coercion in Decision Number 1671/Pdt.G/2024/PA.Sr. The research focuses on the annulment of a marriage resulting from coercion that deprived the parties of their free and genuine consent to marry. Pursuant to Articles 27 and 28 of Law Number 1 of 1974 on Marriage, as amended by Law Number 16 of 2019, and Article 71(f) of the Compilation of Islamic Law, the annulment of a marriage may only be granted by a court decision where a defect in consent, including coercion, is established. This study employs a normative juridical method with a case approach and applies qualitative analysis to statutory regulations, legal literature, and the court decision. The findings reveal that the panel of judges granted the petition for annulment after determining that the marriage had been concluded under psychological and social pressure, thereby eliminating the parties’ free will to consent to the marriage. Consequently, the subjective legal requirements for a valid marriage under Indonesian marriage law and the principles of Islamic law were not fulfilled. The legal consequences include the annulment of the marriage by court decision, the restoration of the parties to their previous legal status, the invalidation of the marriage registration, and the non-existence of marital joint property. Nevertheless, the law continues to protect parties acting in good faith and guarantees the legal status of children born from the marriage. Abstrak Penelitian ini bertujuan untuk menganalisis dasar pertimbangan hakim dan akibat hukum pembatalan perkawinan karena paksaan dalam Putusan Nomor 1671/Pdt.G/2024/PA.Sr. Permasalahan penelitian berfokus pada pembatalan perkawinan yang didasarkan pada adanya paksaan sehingga menghilangkan persetujuan bebas para pihak dalam melangsungkan perkawinan. Berdasarkan Pasal 27 dan Pasal 28 Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan sebagaimana telah diubah dengan Undang-Undang Nomor 16 Tahun 2019 serta Pasal 71 huruf (f) Kompilasi Hukum Islam, pembatalan perkawinan hanya dapat ditetapkan melalui putusan pengadilan apabila terbukti terdapat cacat kehendak berupa paksaan. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan kasus (case approach) serta dianalisis secara kualitatif berdasarkan peraturan perundang-undangan, literatur hukum, dan salinan putusan pengadilan. Hasil penelitian menunjukkan bahwa majelis hakim mengabulkan permohonan pembatalan karena terbukti adanya tekanan psikis dan sosial yang menghilangkan kehendak bebas para pihak dalam memberikan persetujuan perkawinan. Keadaan tersebut menyebabkan tidak terpenuhinya syarat subjektif perkawinan menurut hukum perkawinan nasional dan prinsip hukum Islam. Akibat hukumnya, perkawinan dinyatakan batal berdasarkan putusan pengadilan, para pihak dikembalikan pada status hukum semula, pencatatan perkawinan tidak mempunyai kekuatan hukum, serta harta bersama tidak terbentuk. Namun demikian, hukum tetap memberikan perlindungan kepada pihak yang beritikad baik serta menjamin status hukum anak yang lahir dari perkawinan tersebut.